2021
DOI: 10.3389/fpsyg.2021.627118
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Learning and Mental Health Variables in First-Year Students' Profiles

Abstract: International studies focus on the successful transition into higher education, which is considered crucial for both the students and the educational institution in the context of students' learning and adjustment in higher education. The aim of the current study was to identify student profiles that include cognitive, metacognitive, and motivational aspects of learning, but also aspects of resilience, emotion dysregulation, and anxiety. The sample consists of 316 Greek undergraduate students (18.7% males and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…Universities started to pay attention to students' experiences of successful learning processes, high achievement, and satisfaction as matters of institutional prestige and teaching quality. Simultaneously, national and international policy‐makers increased awareness about the importance of tertiary education as a means of increasing economic competitiveness (Gale & Parker, 2014; Milienos et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Universities started to pay attention to students' experiences of successful learning processes, high achievement, and satisfaction as matters of institutional prestige and teaching quality. Simultaneously, national and international policy‐makers increased awareness about the importance of tertiary education as a means of increasing economic competitiveness (Gale & Parker, 2014; Milienos et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of teaching and learning in higher education (HE) has gained worldwide attention in the last decade (Devlin, 2007;Henard and Roseveare, 2012;Cardoso et al, 2015;Milienos et al, 2021). The new educational vision of higher education is to ensure effective teaching in universities and to be able to determine this effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies exploring mental health factors and approaches to learning are also in line with some of our findings. A study by Milienos et al (2021) of undergraduate students revealed general learner types. At the opposite ends of their groupings were emotionally stable learners, who are emotionally regulated, use a variety of cognitive strategies to learn, and are highly organized and motivated, while those termed emotionally dysregulated learners demonstrate low cognitive involvement in their learning, ambivalence toward learning, and anxiety.…”
Section: Discussionmentioning
confidence: 99%